2021
DOI: 10.1002/eap.2445
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities to reduce pollination deficits and address production shortfalls in an important insect‐pollinated crop

Abstract: Pollinators face multiple pressures and there is evidence of populations in decline. As demand for insect-pollinated crops increases, crop production is threatened by shortfalls in pollination services. Understanding the extent of current yield deficits due to Manuscript

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 59 publications
0
45
0
Order By: Relevance
“…In places where labour is cheap such as some rural areas in Asia, artificial pollination is used to mitigate pollination deficits and improve apple production (Chauhan et al, 2004;Yuan et al, 2016) of a paint brush) and climatic differences could affect the success of artificial pollination (Castro et al, 2016). Hand pollination could suffer from the use of incompatible or otherwise less suitable or low-quality pollen, thus not realizing the full potential of fruit or seed set resulting in a potential underestimation of actual pollination deficits (Aizen & Harder, 2007;Garratt et al, 2021;Wu, Tscharntke, et al, 2021;Wurz et al, 2021). A gradual delivery of pollen by insects may be more effective for fertilizing ovules than the sudden deposition of artificially large amounts of pollen, which may clog stigmas (Ashman et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In places where labour is cheap such as some rural areas in Asia, artificial pollination is used to mitigate pollination deficits and improve apple production (Chauhan et al, 2004;Yuan et al, 2016) of a paint brush) and climatic differences could affect the success of artificial pollination (Castro et al, 2016). Hand pollination could suffer from the use of incompatible or otherwise less suitable or low-quality pollen, thus not realizing the full potential of fruit or seed set resulting in a potential underestimation of actual pollination deficits (Aizen & Harder, 2007;Garratt et al, 2021;Wu, Tscharntke, et al, 2021;Wurz et al, 2021). A gradual delivery of pollen by insects may be more effective for fertilizing ovules than the sudden deposition of artificially large amounts of pollen, which may clog stigmas (Ashman et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, orchards and their surroundings should be managed to improve pollinator communities to harness sufficient insect pollination services and ensure economically and ecologically sustainable crop production (Bänsch et al, 2021;Marini et al, 2012;Sheffield et al, 2016). Garratt et al (2021) reported a significant pollination deficit (measured as yield deficits) in orchards from two European countries (the United Kingdom and Germany) growing three varieties (Gala, Hastings and Braeburn). In our study, with data collected from six European countries, we quantitatively identified an average 30% pollination deficit for fruit set in Europe, with no significant differences between European countries (Figure S4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For higher blossom visit frequency to apple orchards, floral mixes should be tailored towards species preferred by andrenid bees [ 57 , 70 , 230 ]. Evidence suggests that dandelions also enhance andrenid bees, so they can be managed in alleyways as an early flowering resource [ 57 , 169 ].…”
Section: Choice Of Floral Resourcesmentioning
confidence: 99%